2018
DOI: 10.1007/s00784-018-2555-2
|View full text |Cite
|
Sign up to set email alerts
|

Injectable platelet rich fibrin: cell content, morphological, and protein characterization

Abstract: Morphological, cell, and protein characterization of platelet rich fibrin provides a better understanding of the clinical effects and improvement of clinical guidelines for several medical applications. Once well physicochemical and biologically characterized, the use of an injectable platelet rich fibrin can be extended to other applications in the field of orthopedics, periodontics, and implant dentistry on the repairing process of both soft and mineralized tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 41 publications
10
54
0
10
Order By: Relevance
“…All growth factors investigated from I‐PRF (with the exception of BMP‐2) showed the highest release on the first day and decreased thereafter. These changes are consistent with the results observed by Varela et al 35 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…All growth factors investigated from I‐PRF (with the exception of BMP‐2) showed the highest release on the first day and decreased thereafter. These changes are consistent with the results observed by Varela et al 35 …”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, I‐PRF formed a hydrogel‐like small fibrin clot ≈15 minutes after centrifugation and gradually dissolved in the medium. This finding is supported by a recent study which reveals I‐PRF a three‐dimensional fibrin network embedding platelets, leukocytes, osteocalcin, and type I collagen . All growth factors investigated from I‐PRF (with the exception of BMP‐2) showed the highest release on the first day and decreased thereafter.…”
Section: Discussionsupporting
confidence: 81%
“…While our group reported a 33% increase in cell concentrations in i-PRF protocols, other groups have more recently reported similar findings [21]. In a study titled "Injectable platelet-rich fibrin: cell content, morphological, and protein characterization", only a slight increase in platelets (less than 33%) and leukocytes was observed following i-PRF protocols, with decreases in VEGF reported when compared to that in whole blood [21]. Altogether, these studies confirm that previously utilized i-PRF protocols (~60 g for 3-4 minutes on a fixed-angle centrifuge) are inadequately effective at separating blood cell layers owing to their considerable reduction in centrifugation speed and time.…”
Section: Discussionsupporting
confidence: 81%
“…Previously, our research group found that only slight increases in platelets and leukocytes were noted with failure to adequately accumulate cells in the upper plasma layer owing to extremely low RCF values (60 g) and centrifugation times (3-4 minutes) [16]. While our group reported a 33% increase in cell concentrations in i-PRF protocols, other groups have more recently reported similar findings [21]. In a study titled "Injectable platelet-rich fibrin: cell content, morphological, and protein characterization", only a slight increase in platelets (less than 33%) and leukocytes was observed following i-PRF protocols, with decreases in VEGF reported when compared to that in whole blood [21].…”
Section: Discussionsupporting
confidence: 68%
“…La fibrina rica en plaquetas y leucocitos (L-PRF) cuenta ya con suficiente evidencia para transformarse en una alternativa más a considerar al momento de tratar estas secuelas, como por ejemplo: defectos periodontales infra óseos, deficiencias de reborde alveolar, preservación de alveolos post-exodoncia, entre otros (Castro et al, 2017a,b;Nelson et al, 2018). Para la versión inyectable (i-PRF) se describen sus primeras aplicaciones para favorecer la regenera-ción ósea guiada en conjunto con sustitutos óseos, protocolos conocidos como Sticky Bone o PRF-Block (Sohn, 2010;Cortellini et al, 2018), existiendo ya estudios in-vitro en donde miden su contenido celular de plaquetas y leucocitos y liberación de factores de crecimiento como el VEGF, TGF-ß, PDGF, reportando comportamiento similar al del L-PRF Varela et al, 2018). En condiciones fisiológicas, estos factores son responsables del inicio y regulación de la respuesta reparativa.…”
Section: Introductionunclassified